Effect of different organic manures on BLRI developed Napier-4 fodder production in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
An agronomical trial on Napier fodder was conducted to determine the biomass yield and chemical composition with the effect of different sources of organic manures such as biogas slurry, broiler litter and layer litter for fodder production. There was significant (P